Determining factors associated with inhaled therapy adherence on Asthma and COPD treatment - Monteiro, Constança Lourenço Pelicho (2021)
Background: Adherence to therapy has been reported worldwide as a major problem, and that is particularly relevant on inhaled therapy for Asthma and Chronic Obstructive Pulmonary Disease (COPD), considering its barriers and features. It was synthesized the global literature reporting the main determinants for adherence on these patients. Methods: Searches were made in Cochrane Library, MEDLINE, EMBASE and ISI Web of Science databases. Analytical observational epidemiological studies (cohort, case-control and cross-sectional studies) were included, reporting association between any type of determinant and the adherence for inhaler therapy on Asthma or COPD. Randomeffects meta-analysis were used to summarize the numerical effect estimates. Findings: 47 studies were included, giving a total of 54.765 participants. In meta-analyses, the significant determinants of adherence to inhaled therapy were: higher age [RR=1.07 (1.03-1.10); I2=94; p<0.0001] good disease knowledge/literacy [RR=1.37 (1.28-1.47); I2=14; p=0.33]; obesity [RR=1.30 (1.12-1.50); I2=0; p=0.37]; good cognitive performance [RR=1.28 (1.17-1.40); I2=0; p=0.62]; higher income [RR=1.63 (1.05- 2.56); I2=0;p=0.52]; being employed [RR=0.87 (0.83-0.90); I2=0; p=0.76] and using multiple drugs/inhalers [RR=0.81 (0.79-0.84); I2=0; p=0.80]. Overall, the strength of the underlying evidence was only low to moderate. Interpretation: Many determinants may be associated, either to better adherence, such as age, good disease knowledge/literacy, obesity, good cognitive performance and higher income; either to poor adherence, such as being employed or using multiple inhalers. Personalized interventions should be taken in clinical practice to address patient’s adherence according to such features.